Obtenção de conceitos no indivíduo e no grupo - Ferreira, Maria Cristina (1977)
This experiment was designed to compare group and individual performance and verify the influence of group size in the solution of conjunctive concept-attainment problems, using the reception paradigm. The independent variable was group size in three levels, groups of two, three and four individuals. I The major results there: 1) The performance (number of problems correctly solved) in groups of three and four was significantly superior to the individual performance. 2) There were no significative differences between groups of two and individual performance. 3) The performance 1n groups of three and four was significantly superior to those of two individuals. 4) There were no significative differences in performance, between groups of three and four individuals. The results were interpreted folowing the model A, of Lorge and Solomon (1955), which assumes that group performance achieves the level of its best member.